The Bilateral Inheritance System in Islamic Family Law: Fairness, Equality, and Mutual Exchange Perspectives - Aniroh, Reni Nur; Nasution, Khoiruddin; Sodiqin, Ali (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article aims to demonstrate that bilateral inheritance is a system of inheritance that is intended to embody the principles of equal justice in Islamic family law. Hazairin, the pioneer of bilateral inheritance, has initiated the implementation of these principles. However, there are still some issues that need to be addressed in some circumstances. This study employs a juridical legal approach, examining it through the lens of John Rawls' theory of justice and Mubādalah Faqihuddin Abdul Kodir's theory. The studied material consists of notions and perspectives concerning the distribution of inheritance in Islamic law, derived from the Qur’an, hadith, and the viewpoints of ulama and legal professionals. The article's conclusion demonstrates that, according to John Rawls's theory of justice and Mubādalah Faqihuddin Abdul Kodir's theory, bilateral inheritance, when interpreted in a mutually equitable manner, establishes equal positions for men and women in terms of both lineage and inheritance, based on their individual circumstances. Under circumstances where women, like men, can inherit all assets as sole heirs without contravening the explicit restrictions of the text, Furthermore, the allocation of inherited assets can be executed without any complex calculations or meticulous planning, since these assets can be fully utilized without any surplus or diminishing the portion received by the heirs. This essay aims to highlight Hazairin's innovative proposal for ensuring fair treatment in inheritance disputes while also addressing the theological issues that have been overlooked. Consequently, it is possible to examine Hazairin's thesis by employing Rawls' theory of justice and Mubjadi Faqihuddin's theory.